RELATIONSHIP BETWEEN URBANIZATION AND DENGUE HAEMORRHAGIC FEVER INCIDENCE IN SEMARANG CITY - Isnu Putra Pratama; Sri Rahayu (Geoplanning: Journal of Geomatics and Planning, 2016)
Unplanned urbanization can cause unhealthy urban environment, which in turn increases the population of mosquitoes carrying the dengue vector. Consequently, this would reduce the urban life quality because public health is an important aspect of it. The increasing incidence of Dengue Hemorrhagic Fever (DHF) in Semarang City has been alarming. In 2013, the incidence was 2,364 cases, which increased up to 89.11% from the 1,250 cases of 2012. So, it is necessary to study about what relationship is there between the level of urbanization and the incidence of DHF in Semarang. This study used quantitative and spatial approach. The unit of analysis is sub-district with time series data from 2006 to 2013. The analysis technique is spatial analysis through image interpretation, regression, and descriptive analysis. The level of urbanization has been measured through the variables of population growth, population density, land use change, and building density. The results have shown that there is no significant correlation between the level of urbanization and the incidence of dengue fever. The urbanization is acknowledged as influencing only about 28% of the DHF incidence in the city, while the other 72% has been influenced by other factors.